La directive IPPC : où en est-on et où va-t-on ? - Anne Cikankowitz; Valérie Laforest (VertigO)
Since 1996, the implementation of the IPPC Directive (Integrated Pollution Prevention and Control) has been in the middle of public and policies debate. Some non conformities are still present ; the blocking points are not yet solved whereas a new directive on industrial emissions is already proposed. The IPPC Directive requires namely industries concerned by this regulation to use “best available techniques” (BAT). However, at the local level, operators do not have practical tools or simple methods to justify their use of BAT or techniques with equivalent performance. This article focus on the evolution of the regulatory framework related to the implementation of the IPPC Directive since 1996, in Europe and especially in France. It offers an overview of the main blocking points of the IPPC implementation. In conclusion, the article shows that through the analysis of the regulatory context under the IPPC directive in Europe, it is crucial to develop an environmental performance assessment methodology within the meaning of the IPPC.